Exosomes Regulate NLRP3 Inflammasome in Diseases - Li, Zhangwang; Chen, Xinyue; Tao, Junjie; Shi, Ao; Zhang, Jing; Yu, Peng (Frontiers in Cell and Developmental Biology, 2022)
Emerging evidence has suggested the unique and critical role of exosomes as signal molecules vector in various diseases. Numerous researchers have been trying to identify how these exosomes function in immune progression, as this could promote their use as biomarkers for the disease process and potential promising diagnostic tools. NOD-like receptor family, pyrin domain containing 3 (NLRP3), a tripartite protein, contains three functional domains a central nucleotide-binding and oligomerization domain (NACHT), an N-terminal pyrin domain (PYD), and a leucine-rich repeat domain (LRR). Of note, existing studies have identified exosome as a novel mediator of the NLRP3 inflammasome, which is critical in diseases progression. However, the actual mechanisms and clinical treatment related to exosomes and NLRP3 are still not fully understood. Herein, we presented an up-to-date review of exosomes and NLRP3 in diseases, outlining what is known about the role of exosomes in the activation of NLRP3 inflammasome and also highlighting areas of this topic that warrant further study.